Integrity Test for Hepa Filters in Cleanroom Preparation and Cleanroom Process of Labled Compound - I Wayan Widiana; Hermanto Hermanto (Indonesian Journal of Pharmaceutical Science and Technology, 2019)
One of some factors that take effect for the cleanroom sterilization is the integrity of HEPA filters. The value of HEPA filters integrity should be contained in the qualification document of air conditioning system (HVAC). HEPA filters integrity testing aims to ensure the performance of HEPA filters that installed in the air conditioning system, so that no leakage occurs in the installation of HEPA filters, that cause the cleanroom becomes unsterile. The methodology used is to supply aerosol concentration in the upper HEPA filter between 10 - 100 μg/L, and then perform a maximum aerosol penetration measurement on the downstream of HEPA filter. The results are compared with the standard provisions that is contained in the "Procedural Standards for Certified Testing of Cleanrooms", where the maximum permissible penetration is 0.01%. The maximum value of aerosol penetration below 0.01%, that states a HEPA filter has good integrity. While the maximum value of aerosol penetration percentage above 0.01%, states that a HEPA filter has poor integrity. Integrrity test of HEPA filters was performed on 8 units, there are in the cleanroom preparation and cleanroom process of labled compound. The result obtained from the test is that all HEPA filter units have excellent integrity with maximum penetration percentage below 0.01%. The maximum aerosol penetration rate obtained from the overall HEPA filter is 0.004825 % ± 0.000707.Keywords: Labled Compound, Cleanroom, HEPA filter integrity, aerosol penetration